Optimal Controls for a Class of Impulsive Katugampola Fractional Differential Equations with Nonlocal Conditions. (1st December 2020) - Chen, Xingru; Gu, Haibo; Sun, Yu
Abstract : In this paper, we investigate a class of impulsive Katugampola fractional differential equations with nonlocal conditions in a Banach space. First, by using a fixed-point theorem, we obtain the existence results for a class of impulsive Katugampola fractional differential equations. Secondly, we derive the sufficient conditions for optimal controls by building approximating minimizing sequences of functions twice.